A free-energy perturbation study of the binding of methotrexate to mutants of dihydrofolate reductase. - Singh, U C (1988)
The importance of hydrophobic residues to the binding of methotrexate in the active site of dihydrofolate reductase (EC 1.5.1.3) was examined by a free-energy perturbation method. The replacement of a strictly conserved residue, Phe-31, by tyrosine or valine costs 1.8 and 5.1 kcal/mol, respectively, to the binding of the drug (1 cal = 4.184 J). In the case of the Phe31----Tyr mutation, the loss of the binding energy is due to the desolvation of the phenolic group; in the case of Phe31----Val mutation, it is mainly due to the loss of the interaction with the drug. The replacement of Leu-54 by glycine decreases the binding energy by 4.0 kcal/mol. A calculation on the mutation of Phe-31 to serine shows that the alteration could reduce the binding energy of methotrexate by 9.7 kcal/mol. The calculations clearly show that the hydrophobic interactions are as important as the hydrophilic ones in the binding of methotrexate.